The effects of the Gua Sha technique (western view) on the flexibility of the posterior chain: series of cases - Barbalho, Matheus de Siqueira Mendes; Moraes, Paulo Henrique (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The Gua Sha technique is a method from the traditional Chinese medicine (TCM), having its origins in the prehistory, where they had the habit of rubbing their bodies to relieve symptoms of pain. The term “gua” means to scrape, brush, scratch and the term “Sha” has a more complex meaning such as sand or dirt. In China, this technique was and still is very used by the peasants. Gua Sha’s great effects exist by its simultaneous action on the skin, in the connective tissues, in the lymphatic system, in the muscles, blood vessels and the internal organs. Objectives: To verify the Gua Sha technique’s (western view) use in the flexibility recovering of sedentary men. Methods: This study had as sample three men with average of 28,66± years, height of 176cm+=9,29, weight of 100,3kgs±15,05. At first, the study was conducted through the patient’s anamnesis, besides the checking if the patients didn’t have any limitation to perform the evaluation tests. Then, the individuals were submitted to the gua sha technique’s treatment in all their posterior chain, only in one session. Results: After the treatment session using the Gua Sha, the patient’s improvement was notorious. Analyzing the data that shows one gain in about 330 of the lumbar back’s amplitude evaluated by the goniometry and flexibility, through the fingertip-to-floor test, in a short treatment time. In the fingertip-to-floor test, the patients were classified with reduced flexibility, because they stayed more than 10 cm away from the ground, after the technique’s use all patients were classified as having regular flexibility, since they touched the third finger on the floor. Discussion: The Gua Sha technique is very used in the eastern culture for muscular and breathing pains, so this article demonstrates one more accomplishment of the technique, the flexibility gain with satisfactory results, an important factor was the use of only one series obtaining these results, becoming one more technique to add to a combined treatment, aiming the patient’s improvement. Conclusion: This way we conclude that the Gua Sha technique is an excellent tool for the myofascial induction, for the gain of muscular mobility and flexibility of the posterior chain in a short period of treatment time.